Money growth and consumer price inflation in the euro area: A wavelet analysis - Martin Mandler; Michael Scharnagl (Deutsche Bundesbank, 2014)
Our paper studies the relationship between money growth and consumer price inflation in the euro area using wavelet analysis. Wavelet analysis allows to account for variations in the money growth-inflation relationship both across the frequency spectrum and across time. We find evidence of strong comovements between money growth and inflation at low frequencies with money growth as the leading variable. However, our analysis of time variation at medium-to-long-run frequencies indicates a weakening of the relationship after the mid 1990s which also reflects in a deterioration of the leading indicator property and a decline in the cross wavelet gain. In contrast, most of the literature, by failing to account for the effects of time variation, estimated stable long-run relationships between money growth and inflation well into the 2000s.
Keywords: C30; E31; E40; 330; money growth; inflation; wavelet analysis